Synthesis and Characterization of Silver and Gold Nanoparticles Using Aqueous Extract of Seaweed, Turbinaria conoides, and Their Antimicrofouling Activity - Sri Ramkumar Vijayan; Prakash Santhiyagu; Muthukkumarasamy Singamuthu; Natarajan Kumari Ahila; Ravindran Jayaraman; Kannapiran Ethiraj (The Scientific World Journal)
Silver and gold nanoparticles were synthesized using an aqueous extract of the seaweed Turbinaria conoides and their antibiofilm activity against marine biofilm forming bacteria is reported here. The UV-Vis spectra showed the characteristics SPR absorption band for Ag NPs at 421 and for Au NPs at 538 nm. Further, the synthesized nanoparticles were characterized using FT-IR, XRD, FESEM, EDX, and HRTEM analysis. Spherical and triangular nanostructures of the Ag and Au nanoparticles were observed between the size ranges of 2–17 nm and 2–19 nm, respectively. The synthesized Ag NPs are efficient in controlling the bacterial biofilm formation; however, Au NPs did not show any remarkable antibiofilm activity. The maximum zone of inhibition was recorded against E. coli (17.6±0.42 mm), followed by Salmonella sp., S. liquefaciens, and A. hydrophila. The macrotube dilution method inferred the MIC (20–40 µL mL−1) and MBC (40–60 µL mL−1) of Ag NPs. The CLSM images clearly showed the weak adherence and disintegrating biofilm formation of marine biofilm bacterial strains treated with Ag NPs. The Artemia cytotoxicity assay recorded the LC50 value of 88.914±5.04 µL mL−1. Thus the present study proved the efficiency of Ag NPs as a potent antimicrofouling agent and became the future perspective for the possible usage in the biofouling related issues in the aquaculture installations and other marine systems.